(untitled) (El Taco en la Brea, 2024)
That David Viñas, in Argentina, and Carlos Heitor Cony, in Brazil, both writers, are recognized as precursors of the reception of Sartrean Existentialism, there is no doubt. While, however, Un Dios Cotidiano is commonly remembered by critics, at the same time Informação ao Crucificado is forgotten by them. In these novels there are however several proximities, such as a common narrative space —the seminar—; a shared distrust of Christianity; issues that share in images of violence. This paper looks for to compare both books, showing what they keep from the reception of Existentialism in America, at the same time that it points both books to the limits of the French movement and to the possibilities of rupture in its reception in Argentina and Brazil.